PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH KOMPETENSI DAN MOTIVASI GURU TERHADAP KINERJA GURU (Studi Pada Guru PNS di SMK Negeri Kab. Pati) - Dewi Irmayani, 11 52.02 0066 (Students Journal of Economic and Management, 2013)
This study aims to analyze The Influence of Competence and Motivation to the Teachers Performance with the Principal Leadership  as moderate variable at SMK negeri in Pati Regency. This study belongs to the type of quantitative research. Population of this study are 134 teacher, while the samples taken as many as 100 teacher as respondent. Measurements using a Likert scale with 5 (five) alternative answer. Test instruments used are the validity, reliability and classic asumption test. While the test model used is the coefficient of determination and F test (Goodness of Fit). Hypothesis testing used in this study used regression analysis and t-test. The results of the first model showed the coefficient of determination (Adjusted R Square) is 0,541, the meaning of the result is that the Competence and Motivation together have a 54,1% impact to the Techers Performance and the rest are influenced by others variables. Based on the research result can be summarized as follows: (i) Competence is positive and significant effect to the Teachers Performance, (ii) ) Motivation is positive and significant effect to the Teachers Performance, (iii) Principal Leadership is not moderating to the effect of Competence to Teacher Performance, (iv) Principal Leadership is not moderating to the effect of Motivation to Teacher Performance Key words :      Competence, motivation, Principal Leadership, Teachers Performance